AN ARTIFICIAL INTELLIGENCE BASED ADAPTIVE PEDAGOGICAL SYSTEM FOR STUDENTS’ SELF-DEVELOPMENT - Kudenov, Temurbek Maxsetbaevich (SCIENCE and SOCIETY, 2026)
The article explores the theoretical and pedagogical foundations of an artificial intelligence-based adaptive pedagogical system for students' self-development. It provides a scientific justification of the essence, structural components, functions, and the role of the adaptive pedagogical system within a personalized digital learning environment. The study analyzes the potential of artificial intelligence technologies in learning analytics, the design of individualized learning trajectories, pedagogical decision support, and the development of students' self-development competence.
Keywords: artificial intelligence; adaptive pedagogical system; student self-development; personalized learning; digital learning environment; learning analytics; individualized learning trajectory; adaptive learning; higher education